2015
DOI: 10.1073/pnas.1416869112
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of ORF1p is required for L1 retrotransposition

Abstract: Although members of the L1 (LINE-1) clade of non-LTR retrotransposons can be deleterious, the L1 clade has remained active in most mammals for ∼100 million years and generated almost 40% of the human genome. The details of L1-host interaction are largely unknown, however. Here we report that L1 activity requires phosphorylation of the protein encoded by the L1 ORF1 (ORF1p). Critical phospho-acceptor residues (two serines and two threonines) reside in four conserved proline-directed protein kinase (PDPK) target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 76 publications
2
72
0
Order By: Relevance
“…9), the three amino acids forming the conserved salt bridge that stabilize the structure of ORF1p (orange arrows) and the residues providing RNA-binding side chains (green arrows) (Khazina and Weichenrieder 2009). In addition, several motifs involved in the phosphorylation of ORF1p (Cook et al 2015) are conserved, although never across all families (fig. 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9), the three amino acids forming the conserved salt bridge that stabilize the structure of ORF1p (orange arrows) and the residues providing RNA-binding side chains (green arrows) (Khazina and Weichenrieder 2009). In addition, several motifs involved in the phosphorylation of ORF1p (Cook et al 2015) are conserved, although never across all families (fig. 9).…”
Section: Resultsmentioning
confidence: 99%
“…ORF1 contains a coiled-coil domain (CCD), which promotes the formation of ORF1p trimers, a non-canonical RNA recognition motif (RRM) and a highly conserved C-terminus domain (Martin and Bushman 2001; Martin et al 2003; Januszyk et al 2007; Khazina and Weichenrieder 2009). The function of ORF1 remains obscure but it has been shown to have nucleic acid chaperone activity (Martin and Bushman 2001) and recent studies showed that the human ORF1p requires phosphorylation for retrotransposition in a cell culture-based assay (Cook et al 2015). ORF1p participate in the formation of L1 ribonucleoprotein particles (RNP), which is a necessary step of the transposition process (Kolosha and Martin 1997; Kulpa and Moran 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We first determined whether activated wild type p38δ (WT, Invitrogen) could phosphorylate ORF1p on its S/T-P motifs, which are required for robust L1 activity [31]. In vitro radioactive kinase assays revealed that p38δ-WT exclusively phosphorylated bacterially purified ORF1p on these residues, as an ORF1p carrying mutations at all four motifs, S18A/S27A/T203G/T213G (AAGG), was not phosphorylated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting clone was designated pET32aΔN. Full-length ORF1 PCR-generated amplicons were created from the previously described pORF1-Flag mammalian expression vector [31] using a high-fidelity DNA polymerase with the forward primer 5′CGCGGATCCATGGGGAAAAAACAGAACAG containing a 5′ BamH1 site, and reverse primer 5′GCCGGAATTCGCCGCCGCCCATTTTGGCATGATTTTGC, which introduced a spacer of three glycines between the end of ORF1 and the 3′ EcoRI sequence (the Flag sequence was not retained). The ORF1p amplicon was inserted into pET32aΔN via the BamH1 and EcoRI sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation